Activating Specific Handball's Defensive Motor Behaviors in Young Female Players: A Non-Linear Approach - Sebastián Espoz-Lazo; Claudio Farías-Valenzuela; Claudio Hinojosa-Torres; Frano Giakoni-Ramirez; Pablo Del Val-Martín; Daniel Duclos-Bastías; Pedro Valdivia-Moral (MDPI AG, 2023)
Traditional models to train and teach young players in team sports assume that athletes learn as linear systems. However, an actual methodology called Non-Linear Pedagogy (NLP) accounts for the fact that the players and the team are complex dynamic systems. Experiences in handball under this methodology are scarce; due to this, an observational study has been conducted with a follow-up, idiographic and multidimensional design, in which 14 female school handball players belonging to four different local teams in Santiago, Chile (age = 15.55 + 0.51) agreed to participate in three special handball training sessions with the use of the NLP methodology where three different constraints were used. Descriptive analysis with the Chi-squared test showed a total of 252 observations where most of the variables were dependent on the constraints (p ≤ 0.001). Frequency showed that mainly "Defense in Line of progression" and "Proximal contact" were the most activated variables, followed by "Harassment" and "Deterrence" for all constraints. However, only constraint 2 highly activated two collective motor behaviors, while the rest only did it with individual motor behaviors. It is concluded that the constraints used in training seem to be effective in activating a group of defensive handball motor behaviors, specifically those that are basic for female school handball players.